1966
DOI: 10.1002/1520-6807(196601)3:1<79::aid-pits2310030122>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics of high school male and female potential scientists in comparison with academic underachievers

Abstract: Brown University has undertaken two programs of special education for secondary school students-one for bright, academically successful, boys and girls who have demonstrated outstanding potential for careers as scientists, the other for boys who possess the intellectual potential for high achievement but who are failing academically. This paper reports some personality, motivational, and social characteristics revealed by these young men and women who are travelling smoothly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1969
1969
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…A somewhat similar study reported by Davids (1966) showed that one major difference between over-and under-achievers among "potential scientists," as judged by high science aptitude scores, was that overachievers scored significantly higher on the Ai scale than did underachievers. Domino (1969) examined the performance of 348 college juniors in courses which were divided into two operationally defined categories: those rewarding independent behavior of students, and those rewarding conforming behavior.…”
Section: Achievement Via Independencesupporting
confidence: 57%
“…A somewhat similar study reported by Davids (1966) showed that one major difference between over-and under-achievers among "potential scientists," as judged by high science aptitude scores, was that overachievers scored significantly higher on the Ai scale than did underachievers. Domino (1969) examined the performance of 348 college juniors in courses which were divided into two operationally defined categories: those rewarding independent behavior of students, and those rewarding conforming behavior.…”
Section: Achievement Via Independencesupporting
confidence: 57%
“…al. (1966) study, andthe Davids (1966) study, indicate that the personal adjustment of gifted males during the college years may not be as positive as Terman's ratings suggest.…”
Section: Discussionmentioning
confidence: 89%
“…Although several studies have examined the personality characteristics of gifted and nongifted college students using the CPI (Chambers & Dusseault, 1972;Mason, Adams, & Blood, 1966;Mason & Blood,1966), only Davids (1966) reported results separately for males and females. He administered CPI's to college students at Brown University who had been identified as potential scientists.…”
Section: Discussionmentioning
confidence: 99%
“…This reasoning is borne out by empirical research. Among intellectually superior college students, those achieving at high levels have been found to show favorable adjustment patterns (Davids, 1966;Nichols, 1967;Pollins, 1983).…”
Section: Introductionmentioning
confidence: 99%